Vehicles, Drivers, and Safety - Abut, Huseyin; Hansen, John; Schmidt, Gerhard; Takeda, Kazuya (De Gruyter, 2020)
This book presents works from world-class experts from academia, industry, and national agencies representing countries from across the world focused on automotive fields for in-vehicle signal processing and safety. These include cutting-edge studies on safety, driver behavior, infrastructure, and human-to-vehicle interfaces. Vehicle Systems, Driver Modeling and Safety is appropriate for researchers, engineers, and professionals working in signal processing for vehicle systems, next generation system design from driver-assisted through fully autonomous vehicles.
Keywords: Signal processing -- Digital techniques.; Motor vehicles -- Electronic equipment.; Automobiles -- Safety measures.; Automotive telematics.; elektronické knihy; electronic books